EFFECT OF RHIZOBIUM ON GROWTH OF DIFFERENT MUNGBEAN VARIETIES UNDER SALT STRESS CONDITIONS - Ullah, Muhammad Arshad; Baber, Raheel; Hyder, Syed Ishtiaq; Sultan, Tariq; Mahmood, Imdad Ali; Ullah, Kaleem (JOURNAL OF ADVANCES IN NATURAL SCIENCES, 2016)
Excessive and imbalanced use of chemical fertilizers may pose devastating effect on soil fertility and sustainable productivity. Bio-organic amendments improve soil fertility and sustainable crop productivity. Seeds of mungbean varieties i.e. NCM-2013, Chackwal-Mung 06, NM-11 and AZRI-06 were inoculated with rhizobium in saline soil. These inccilated miunngbean varieties were sown under artificially salinity developed soil (ECe= 5.0 dSm-1) using completely randomized design with three repeats for enhancement of growth. The experiment was conducted during July to September, 2015 in the Head House of Land Resources Research Institute, National Agricultural research Centre, Islamabad, Pakistan. Data were collected on germination, plant height, root length, fresh / dry weight and chlorophyll contents during experiment period. Ionic concentrations of P, Cu, Fe, Mg and Zn were determined to compare the difference of edible quality in saline soil under the inoculation of seeds with rhizobium. Effect of biozote on germination, root length, fresh weight and dry weight was significant in all mung bean varieties: NCM-2013, Chakwal Mung-06, NM-II and AZRI-06 under salt stress conditions. Maximum germination (53%) was recorded by Chakwal Mung-06 followed by 51% by AZRI-06. The maximum root length (10.1 cm) was registered by NM-II. Fresh weight / plant was maximum (5.1 g) by AZRI-06. The maximum dry weight/plant (1.5 g) was recorded by AZRI-06. Maximum P% (0.14), Cu (4.83 ppm), Fe (179.3ppm), Mg (2.07ppm) and Zn (168.8ppm) of Chakwal Mung-06 with the use of rhizobium under salt stress by NM-11. Similar trend was also recorded in ionic concentration of P, Cu, Fe and Mg by NM-11 without rhizobium under salt stress conditions.. The saline soil affected the quality of mungbean showing the reduction under salt stress without rhizobium inoculation in ionic concentration. The results of ionic values showed that NM-11 attained the highest position following the AZRI-06. [3] and [8] reported same results regarding K and P of different crops under salt stress conditions.